2015
DOI: 10.1007/s40489-015-0055-8
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental Motor Skills and School-Aged Individuals with Visual Impairments: a Review

Abstract: The purpose of this paper was to review the published research literature on fundamental motor skills (FMS) for school-aged individuals with visual impairment by describing study characteristics and major findings of the extant literature. Keyword searchers were used to identify articles from electronic databases published between 1982 and 2014. Eleven articles met all inclusion criteria, and relevant data were extracted from them. Of the 11 studies, six were comparative, two were correlational, two were valid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
26
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 26 publications
1
26
0
2
Order By: Relevance
“…Nevertheless, significant differences between children with and without visual impairment on single-leg balance performance were registered (Uzunović, 2015). Researchers found evidence to support delays in motor acquisition of school-aged individuals with visual impairments compared to age-matched eye-sighted counterparts without such disa bi lities (Haegele ET AL., 2015). In general, the studies confirmed that visually impaired children have a lower level of health-related physical fitness than their eye-sighted peers (Kozub & Oh, 2004, Lieberman et al, 2002.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, significant differences between children with and without visual impairment on single-leg balance performance were registered (Uzunović, 2015). Researchers found evidence to support delays in motor acquisition of school-aged individuals with visual impairments compared to age-matched eye-sighted counterparts without such disa bi lities (Haegele ET AL., 2015). In general, the studies confirmed that visually impaired children have a lower level of health-related physical fitness than their eye-sighted peers (Kozub & Oh, 2004, Lieberman et al, 2002.…”
Section: Discussionmentioning
confidence: 99%
“…Overweight constitutes one of the greatest problems of the 20 th century [15]. In Poland, it concerns 20% of children and youth [34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…Their daily activity requires a lot of energy compared with healthy peers. Exercises are a preventative measure for them and give them the opportunity to improve weakened functions [14][15][16][17][18][19]. Low physical activity among disabled people is not a new phenomenon; despite this, there are very few scientists interested in the subject.…”
Section: Introductionmentioning
confidence: 99%
“…In a sample of children and adolescents aged 6-20 years old reported that people with visual impairment (VI) are more inactive compared to individuals with hearing loss and some types of physical impairment [2,4]. Major findings suggest that, in comparison to peers without disabilities, those with visual impairments tend to perform significantly greater delays in fundamental motor skills (FMS) [5]. Children who are blind are at greater risk of falling due to poor balancing skills [6].…”
Section: Introductionmentioning
confidence: 99%